Electrospun Poly(ε-caprolactone)/Poly(ethylene glycol) Nanofibers Loaded with Artemisia absinthium Extract for Wound Healing Properties - Selcuk Pekdemir, Sibel; Pekdemir, Mustafa Ersin; Birhanli, Emre; Kurucay, Ali; Ulu, Ahmet; Qader, Ibrahim Nazem; Ates, Burhan (Springer, 2026)
The lack of intrinsic antibacterial and antioxidant properties in conventional polymer-based wound dressings limits their effectiveness in tissue regeneration. This study presents a novel multifunctional electrospun PCL/PEG nanofiber scaffold incorporating Artemisia absinthium extract (5-30 wt%), a bioactive plant agent not previously integrated into polymeric wound dressings. ATR-IR and thermal analyses confirmed successful incorporation of the extract without disrupting the structural integrity of the fibers. The extract increased fiber hydrophilicity and introduced strong antioxidant activity, reaching its highest effect at 10 wt% loading. Antibacterial assays revealed concentration-dependent inhibition. At non-toxic concentrations, the produced materials did not exhibit antibacterial effects. However, they demonstrated improved antimicrobial efficacy compared to neat PCL/PEG fibers, particularly against Staphylococcus aureus. Cytotoxicity and in vitro wound healing tests showed that <= 10 wt% extract maintained excellent biocompatibility and enhanced fibroblast proliferation, whereas >= 20 wt% reduced cell viability. These findings clearly demonstrated that integrating Artemisia absinthium into nanofiber scaffolds offers an advantageous and biologically active alternative material by simultaneously providing antioxidant and biocompatible performance.
Keywords: Electrospun Nanofibers; Artemisia Absinthium; Antibacterial Activity; Wound Healing; Antioxidant Properties